Analisis Faktor-Faktor Penentu Dividend Policy Pada Perusahaan Publik Sektor Makanan dan Minuman - Nurul Fuada; Amiruddin Amiruddin; Syarifuddin Rasyid; Darmawati; Rahmawati Hs (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to identify the determinants of dividend policy based on financial ratio data. The determinants of dividend policy consist of Return on Asset (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), dan Price to Earning Ratio (PER). The sample of this research is public companies in the food and beverage sector. The results of this study indicate that the determinants consisting of ROA, CR, DER, and PER have no effect on dividend policy which indicates that the number of financial ratios from the value of ROA, CR, DER and PER does not encourage the amount of dividend policy. Thus, companies in making dividend distribution decisions tend to be more determined by other variables than ROA, CR, DER, and PER.